Randomized Pilot Clinical Trial of Early Coronary Angiography Versus No Early Coronary Angiography After Cardiac Arrest Without ST-Segment Elevation: The PEARL Study. Issue 21 (24th November 2020) - Kern, Karl B.; Radsel, Peter; Jentzer, Jacob C.; Seder, David B.; Lee, Kwan S.; Lotun, Kapildeo; Janardhanan, Rajesh; Stub, Dion; Hsu, Chiu-Hsieh; Noc, Marko
Abstract : Background: The benefit of emergency coronary angiography after resuscitation from out-of-hospital cardiac arrest is uncertain for patients without ST-segment elevation. The aim of this randomized trial was to evaluate the efficacy and safety of early coronary angiography and to determine the prevalence of acute coronary occlusion in resuscitated patients with out-of-hospital cardiac arrest without ST-segment elevation. Methods: Adult (>18 years) comatose survivors without ST-segment elevation after resuscitation from out-of-hospital cardiac arrest were prospectively randomized in a 1:1 fashion under exception to informed consent regulations to early coronary angiography versus no early coronary angiography in this multicenter study. Early angiography was defined as ⩽120 minutes from arrival at the percutaneous coronary intervention–capable facility. The primary end point was a composite of efficacy and safety measures, including efficacy measures of survival to discharge, favorable neurologic status at discharge (Cerebral Performance Category score ⩽2), echocardiographic measures of left ventricular ejection fraction >50%, and a normal regional wall motion score of 16 within 24 hours of admission. Adverse events included rearrest, pulmonary edema on chest x-ray, acute renal dysfunction, bleeding requiring transfusion or intervention, hypotension (systolic arterial pressure ⩽90 mm Hg), and pneumonia. Secondary end points included the incidence of culprit vessels with acute occlusion. Results: The study was terminated prematurely before enrolling the target number of patients. A total of 99 patients were enrolled from 2015 to 2018, including 75 with initially shockable rhythms. Forty-nine patients were randomized to early coronary angiography. The primary end point of efficacy and safety was not different between the 2 groups (55.1% versus 46.0%; P =0.64). Early coronary angiography was not associated with any significant increase in survival (55.1% versus 48.0%; P =0.55) or adverse events (26.5% versus 26.0%; P =1.00). Early coronary angiography revealed a culprit vessel in 47%, with a total of 14% of patients undergoing early coronary angiography having an acutely occluded culprit coronary artery. Conclusions: This underpowered study, when considered together with previous clinical trials, does not support early coronary angiography for comatose survivors of cardiac arrest without ST elevation. Whether early detection of occluded potential culprit arteries leads to interventions that improve outcomes requires additional study. REGISTRATION: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02387398. Abstract : Supplemental Digital Content is available in the text.